Toleransi dan pluralisme: peran toleransi dalam memperkuat pluralisme di indonesia sebagai negara multikultural - Nur Khosimah, Dina Lailatun (Maliki Interdisciplinary Journal, 2026)
With more than 300 ethnic groups and hundreds of different regional languages, Indonesia showcases the rich diversity of this people. This diversity reflects the fact that its varied cultures and histories constitute a unique asset for the consequently, the phenomena of pluralism and multiculturalism have become defining characteristics of Indonesia’s identity. However, this diversity also present unique challenges for Indonesia. This forms the focus of this paper’s objective: to understand the importance of tolerance in addressing these challenges and issues. In this multicultural society, creating social harmony is not easy. One of factors the greatly influences the maintenance of this harmony is tolerance and the strengthening of cultural pluralism.